The effect of forward head posture on cervical joint position sense - Sajjadi, Elaheh; Olyaei, Gholam Reza; Talebian, Saeed; Hadian, Mohammad-Reza; Jalaie, Shohre (Archives of Advances in Biosciences, 2014)
A number of studies have investigated the effect of age, trauma, disease and fatigue on cervical joint position sense. However, there is an absence in data regarding the role of posture on proprioception. The aim of the current study was to investigate the effect of Forward Head Posture (FHP) on cervical joint position sense. Twenty Forward Head Posture volunteers (14 women, 6 men), with the mean age of 23.94 (SD=3.26) years, and 17 normal head posture volunteers (8 women, 9 men) with the mean age of 23.50 (SD=2.68) years were asked to perform the Cervicocephalic relocation test (CRT) to the neutral head position (NHP). The aim of this test was to evaluate the participants’ ability to relocate the head to neutral position after they actively rotated it to left and right sides. Three trials were performed for each rotation to the left and right. In order to assess cervical joint repositioning accuracy, Absolute, Constant and Variable errors were used. No significant difference in repositioning errors was observed between experimental and control group in absolute and constant errors (P>0.05); however, compared to normal group, Forward Head Posture subjects manifested significantly higher levels of variable errors (P<0.05). Forward Head Posture can significantly affect the positioning consistency of cervical proprioception. Nonetheless, further investigation on the effect of Forward Head Posture on cervical proprioception in altered situations is recommended.